Antimicrobial activity of mesophilic and psychrotrophic microfungi isolate from: King George Island and Greenwich Island, maritime Antarctica / Wessam Mansour Filfilan - Filfilan, Wessam Mansour (2012)
This research was made to study the antimicrobial activity of fungal isolates from different regions of maritime, Antarctica, namely, King George Island and Greenwich Island (Barrientos Island, Dee Island and Ambato point). A total of 17 isolates composed of 7 mesophilic and 10 psychrotrophic fungi were tested in-vitro against Gram-positive, Gram-negative bacteria and yeast human pathogens. Initial antimicrobial activity screening of Antarctic isolates was made using plug assay method. Five test-microorganisms namely Candida albicans, Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa were used. Only five (out of 17) fungal isolates showed inhibition potency against the test-microorganisms and majority showed antibacterial activity rather than antifungal activity. Of these five species, three were psychrotrophic and two were mesophilic fungi. It should be pointed out that only two of the screened isolates inhibited the growth of Candida albicans despite the clearing zone diameter was smaller than 20mm. Based on these result, the five fungal isolates with good inhibition potency were selected for further studies. These species were then tested against large number of test-microorganisms by disc diffusion method. That showed only two fungal strains Penicillium sp. 20 and Deuteromycete sp. 25 have antibacterial activity against P. aeruginosa and B. cereus. Later, quantification assay using broth microdilution method was performed to determine the minimum inhibitory concentration (MIC) that showed from 12.5-25 mg/ml, minimum bactericidal concentration (MBC) showed between 25–1.56 mg/ml and minimum fungicidal concentration (MFC). The break point of minimum inhibitory concentration (MIC) was confirmed using indicator dye and both minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) were confirmed by sub-culturing from the different dilutions of crude extract.